Dynamic translocation of Inside-Out proteins to the cell surface underlies cellular adaptation to cancer-induced stress - Tomasz Slezak; Kelly M. O’Leary; Tanya Guevara Avella; Natalia Musial; Jinyang Li; Anna Andrzejczak; Elizabeth F. Scott; Duc Anh Le; Anthony A. Kossiakoff (Proceedings of the National Academy of Sciences, 2026)
Inside-Out (I-O) protein display, the noncanonical surface localization of intracellular proteins, represents an underexplored feature of tumor cell biology. Here, we map the molecular landscape and trafficking mechanisms that control the presentation of I-O proteins on cancer cell membranes. Employing APEX2-mediated proximity biotinylation and a custom antibody generation and validation platform, we identified approximately 140 high-confidence I-O proteins, primarily ribosomal, proteasomal, chaperone, and translation factors, notably enriched in protein families associated with stress-response pathways. Validation of 500 antibodies encompassing 40 I-O targets across seven tumor cell lines confirmed selective and robust surface localization, while in vivo imaging in mouse xenografts demonstrated pronounced and tumor-specific antibody accumulation. I-O proteins were absent on peripheral blood mononuclear cells (PBMCs) and in normal tissues, indicating cancer cell selectivity. Functional analyses revealed that I-O protein tethering to the membrane is dependent on heparan sulfate interactions; enzymatic removal of these glycans led to the clearance of I-O proteins from the cell surface. Notably, the removed proteins returned to baseline levels within 6 h, indicating a dynamic balance related to Endoplasmic Reticulum (ER)-Golgi trafficking and cellular stress. Nearly half of these I-O proteins overlapped with known stress granule (SG) components; however, stress elements that promote SG formation do not similarly affect surface display of I-O proteins. Furthermore, I-O proteins are present on standard cancer cell lines under lower stress levels needed to induce SG formation, suggesting parallel yet mechanistically distinct aspects of the stress response. These findings position I-O display as a paradigm in protein trafficking, different from traditional secretion pathways and closely linked to stress response.